The effects of production parameters on the electrical resistivity of Cu/M7C3-M23C6 MMCs - Yilmaz, O; Aksoy, M (Elsevier Science Sa, 2001)
In this study, the effects of production parameters on the electrical conductivity of the electrofriction material (Cu/M7C3-M23C6) for collectors have been investigated. For this reason; copper and FeCr powders (M7C3-M23C6) were mixed in a mixer in ratios of 5, 10, 15, 20, 30 and 40 wt.% FeCr for 3 h. The pressure was applied as 380, 635, 955 MPa to produce samples having 5 mm radius and 1 mm thickness. Also temperature was changed as 700, 800, 900 degreesC during sintering. After sintering, electrical resistivity measurements, metaleographic investigations and energy dispersive spectrometry (EDS) analysis of the samples have been taken. Finally, it was detected that electrical resistivity was decreased by increasing sintering temperature and compression pressure, and increased depending on additive (FeCr particulates) amount. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: powder metallurgy; composities; sintering; electrical conductivity